Integrating postmodern and postcolonial approaches into teacher education and professional development for the inclusion of refugee and migrant students - Μανιάτης Παναγιώτης; Ρουσσάκης Ιωάννης (Education Sciences, 2025)
The paper examines the education and training of teachers to support refugee and migrant students, focusing on the integration of postcolonial approaches, such as the “Third Space”, which can contribute to the reconstruction of cultural identities and the creation of new forms of knowledge, and “Border Pedagogy”, which encourages the questioning of established power structures and relations to promote social justice. The paper highlights the need for holistic approaches in teacher education and training that build on the experiences of educators and learners, and the dialectical relationship between theory and practice, challenge unilateral cultural boundaries, and aim to develop critical literacies. These approaches position teachers as central agents of inclusion and quality education with a focus on social justice.